Prolonged Response of a Patient with Relapsed Acute Myeloid Leukemia to a Novel Oral Bromodomain Extraterminal Inhibitor (BETi) - Chang Muñoz, Meilen; Murphy, Jennifer A.; Wolff, Johannes E.; Jonas, Brian A. (Case Reports in Hematology, 2020)
Acute myeloid leukemia (AML) is an aggressive clonal bone marrow cancer characterized by high rates of relapse and mortality. A middle-aged woman with AML relapsed twice after achieving complete remission with induction therapy and subsequent salvage therapy. She was then enrolled in a clinical trial with the bromodomain extraterminal inhibitor (BETi) mivebresib and achieved complete remission with incomplete count recovery (CRi) with monotherapy. Subsequently, she relapsed and was transitioned to combination therapy with mivebresib plus venetoclax and achieved CR again. The patient required eltrombopag to decrease platelet dependence in both arms of the trial and exhibited less myelosuppression with the combination therapy. The exceptional response to mivebresib demonstrated by this patient underscores the therapeutic potential of mivebresib.